Syamrotul Aini Pengaruh Media Pembelajaran Berbasis Youtube Terhadap Hasil IPA Siswa Pada Tema Organ Gerak Hewan anan Manusia Di Kelas V SD Negeri 1 Cakat Raya Tulang Bawang - Aini, Syamrotul; Mashari , Ali; Qomario, Qomario (Gayaku Publisher, 2023)
The background of this research is the lack of use of media in the YouTube-based learning process with student learning outcomes in science on the theme of the organs of movement of animals and humans in class V SD Negeri 1 Cakat Raya Tulang Bawang. This study aims to describe whether there is an effect of YouTube-based learning media on students' science learning outcomes on the theme of animal and human movement organs in class V SD Negeri 1 Cakat Raya Tulang Bawang. The survey results of the researchers found that students' science learning outcomes were still low. The method used in this study was quantitative with a pre-experimental method by design of a one group pretest-posttest design. The population in this study was students of class V SD Negeri 1 Cakat Raya Tulang Bawang. The research sample consisted of 24 students. The sampling technique uses a purposive sampling technique. The data collection technique uses tests, documentation, data analysis techniques and uses a t-test.The results of the study are shown by the results of the t-test (paired sample t test) for the same sample with different treatment (pretest-posttest) with a t count of 12.503 and a t table of 1.711. learn science students on the theme of the organs of movement of animals and humans.